2021
DOI: 10.1002/uog.23596
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pregnancies with recent primary cytomegalovirus infection in first trimester treated with hyperimmunoglobulin: observational study

Abstract: What are the novel findings of this work? Primary cytomegalovirus (CMV) infection in the first trimester carries a substantial risk of developmental disorder after birth. We found that hyperimmunoglobulin (HIG) treatment can prevent maternal-fetal CMV transmission if patients are well selected. What are the clinical implications of this work? Administration of HIG should be discussed in cases of a primary CMV infection in the first trimester. HIG treatment is mostly successful in women with a recent primary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 33 publications
3
29
0
5
Order By: Relevance
“…Revello et al conducted a randomized trial and found that this treatment did not significantly modify the course of primary CMV infection during pregnancy [ 23 ]. However, Kagan et al reported that HIG was effective for women with a recent primary infection in the first trimester or during the periconceptional period and when HIG was administered at a biweekly dose of 200 IU/kg [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Revello et al conducted a randomized trial and found that this treatment did not significantly modify the course of primary CMV infection during pregnancy [ 23 ]. However, Kagan et al reported that HIG was effective for women with a recent primary infection in the first trimester or during the periconceptional period and when HIG was administered at a biweekly dose of 200 IU/kg [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, whether using valacyclovir during pregnancy for prevention and treatment of congenital CMV infection is beneficial still remains to be confirmed ( 29 ). In an observational study, hyperimmunoglobulin treatment at a biweekly dose of 200 IU/kg seemed to be potentially useful among women with a recent primary infection in the first trimester or during the periconception period ( 30 ). Thus, offering effective vaccination to susceptible women before conception may also be possible in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the new pharmacological study indicating that the half time of HIG is only about 10 days [ 112 , 113 ], a new investigation was recently undertaken in 149 pregnant women and 153 fetuses to study the efficacy of HIG in pregnant women with a very recent PI in the first trimester or during the periconceptional period with treatment starting at a median gestational age of 10.6 weeks and ending at 17.9 weeks. During this time, IV treatment with HIG was administered on the average only 4 times (every 2 weeks) until about 18 weeks of gestation at the HIG dosage of 200 IU/kg bodyweight [ 114 ]. Very recent PI in the first trimester of pregnancy along with timely initiation of treatment and an appropriate treatment dosage and interval were the parameters preventing maternal-fetal transmission.…”
Section: Preventionmentioning
confidence: 99%
“…This allows seronegative women at risk for PI to be identified and benefit from information about hygienic measures for primary prevention of PI [ 106 ]. In addition, PI can be diagnosed early and treatments for secondary prevention (i.e., prevention of virus transmission to the fetus and congenital disease [ 114 , 118 ]) can be proposed. Although serological screening during or before pregnancy is not universally recommended [ 15 ], we believe, on the basis of the results herein reported, that the approach here described allows a number of congenital infections as well as unnecessary pregnancy terminations to be prevented.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%